Improvement of differential modal gain in few‐mode fibre amplifier by employing ring‐core erbium‐doped fibre. Issue 2 (1st January 2015) - Ono, H.; Hosokawa, T.; Ichii, K.; Matsuo, S.; Yamada, M.
Abstract : The differential modal gain (DMG) in a few‐mode erbium‐doped fibre amplifier (FM‐EDFA) is successfully improved by employing a ring‐core FM erbium‐doped fibre (RC‐EDF). The DMGs between LP01 and LP11 mode signals in the FM‐EDFA with the RC‐EDF are 1.8 and 1.6 dB for LP01 and LP11 mode pumping, respectively, whereas those in a FM‐EDFA with a conventional step‐index FM EDF are 9.2 and 6.1 dB, indicating 7.4 and 4.5 dB DMG improvement for LP01 and LP11 mode pumping, respectively.